Studi Implementasi Nilai Shale Rating Batulanau dalam Penentuan Alat Gali di PT Bintang Prima Energi Pratama Kabupaten Kutai Kartanegara Provinsi Kalimantan Timur - Natalis Pasereng; Windhu Nugroho; Agus Winarno (Venus: Jurnal Publikasi Rumpun Ilmu Teknik, 2024)
The activity of dismantling shale sometimes does not align with the rating of the shale itself. Although shale generally has low durability, some types of shale exhibit considerable strength. Therefore, if the tools used are not suitable, the excavation process becomes inefficient. One shale classification method proposed by Franklin (1982) is by determining the value of slake durability index, plasticity index, and point load index. If the slake durability value exceeds 80 percent, testing continues with point load testing. However, if the slake durability value is below 80 percent, then liquid limit and plastic limit tests are conducted to obtain its plasticity index. This study is applied to the Kampungbaru Formation at PT Bintang Prima Energi Pratama. The shale testing results of the Kampung Baru Formation at PT Bintang Prima Energi yielded slake durability index values below 80 percent, thus the shale ratings based on slake durability index and plasticity index values, for KB1BL1 are 4.2; KB1BL2: 3.5; KB1BL3: 2.55; KB1BL4: 3.35; KB1BL5: 3.15; and KB1BL6: 3.65. With an average shale rating value of 3.57. The excavation tool used for these rocks is a backhoe.